Russian Size Adjectives Analyses by Corpus Linguistics Methods - Gizatullina, Azaliya Rishatovna; Lutfullina, Gulnara Firdavisovna; Yulievna, Tameryan Tatiana (International Journal of Criminology and Sociology, 2022)
The paper analyzes the functioning of size adjectives, exact as well as average size adjectives in Russian. Accurate measurement requires a numeral and also an adjective corresponding to the unit of measure. A parametric adjective is non-obligatory, while the designated parameter is derived from the semantics of the defined noun. The parametric noun in the required case form is included in the noun group, which performs the function of the attribute. Average size adjectives with abstract parameter nouns form complex attributes, taking pre and post positions to the defined noun. The adjective cредний /average is mainly combined with height and length parameters with the dominance of the noun size. Size adjectives короткий / short and длинный / long have a 2.4 asymmetrical ratio index of their functioning. It should be noted that roads and streets are more often characterized by positive and negative parameters, in turn. Adjectives of a positive width parameter dominate in garment characterization. This survey's primary objective is a qualitative analysis of the structure and semantics of size adjectives of exact measurement.